Changes of high altitude glaciers in the Trans-Himalaya of Ladakh over the past five decades (1969-2016) - Schmidt, Susanne; Nüsser, Marcus (Geosciences, 2017)
Climatic differences between monsoonal and cold-arid parts of the South Asian mountain arc account for the uncertainty regarding regional variations in glacier retreat. In this context, the upper Indus Basin of Ladakh, sandwiched between the Himalayan and Karakoram ranges, is of particular interest. The aims of the present study are threefold: to map the glaciers of central and eastern Ladakh, to describe their regional distribution and characteristics in relation to size and topography, and to analyze glacier changes in the selected ranges over the past five decades. The study is based on multi-temporal remote sensing data (Corona and Landsat), supported and validated by several field campaigns carried out between 2007 and 2016. A glacier inventory was carried out for the complete study area, which was subdivided into nine sub-regions for comparison. In general, the glaciers of Ladakh are characterized by their high altitude, as 91% terminate above 5200 m, and by their relatively small size, as 79% of them are smaller than 0.75 km2 and only 4% are larger than 2 km2. The glaciated area of central Ladakh totaled 997 km2 with more than 1800 glaciers in 2002.